2019
DOI: 10.1136/bmjsem-2019-000663
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for falls prevention in community-dwelling older adults: trial and participant characteristics, interventions and bias in clinical trials from a systematic review

Abstract: IntroductionThere is strong evidence that exercise prevents falls in community-dwelling older people. This review summarises trial and participant characteristics, intervention contents and study quality of 108 randomised trials evaluating exercise interventions for falls prevention in community-dwelling older adults.MethodsMEDLINE, EMBASE, CENTRAL and three other databases sourced randomised controlled trials of exercise as a single intervention to prevent falls in community-dwelling adults aged 60+ years to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 133 publications
2
46
1
3
Order By: Relevance
“…We are uncertain of the effect of resistance exercise (without balance and functional exercises), dance, or walking on the rate of falls. The programs evaluated in the trials found to prevent falls included a total program duration that ranged from 5 weeks to 2.5 years, with total hours of exercise ranged from 6 to 312 h. Further program characteristics for types of exercise found to be effective in falls prevention have been carefully evaluated in a previous review [9]. There was a suggestion of a dose-response relationship of exercise on rate of falls (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are uncertain of the effect of resistance exercise (without balance and functional exercises), dance, or walking on the rate of falls. The programs evaluated in the trials found to prevent falls included a total program duration that ranged from 5 weeks to 2.5 years, with total hours of exercise ranged from 6 to 312 h. Further program characteristics for types of exercise found to be effective in falls prevention have been carefully evaluated in a previous review [9]. There was a suggestion of a dose-response relationship of exercise on rate of falls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The large numbers of older people globally and the long-term consequences of falls and fall-related injuries for individuals and health systems make it particularly important that the latest research is summarised regularly to confirm or modify conclusions from previous reviews. Different exercise programs may have different effects on falls and so careful analysis of the characteristics and impact of different programs is important [9]. This systematic review was undertaken to inform the World Health Organization guidelines on Physical Activity and Sedentary Behaviour [10] and involved an update of the Cochrane Review of randomised controlled trials published in 2019 [11] that found high certainty evidence that exercise interventions reduced the rate of falls by 23% in community-dwelling older people compared with controls (rate ratio (RaR) 0.77, 95% confidence interval (CI) 0.71 to 0.83; 12,981 participants, 59 studies).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, while our sample is representative of older Australians’ age, BMI and cultural background, it included a relatively high proportion of females with a small proportion of male participants. Although the risk and incidence of falls are greater in females, males are commonly under-represented in exercise intervention trials [ 60 , 61 ]. Males have been reported to have specific preferences and characteristics of exercise interventions that are most likely to appeal to them [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…They highlight that Tai Chi is one way of providing a safe means of challenging balance. Indeed, in another review paper of 108 trials, Tai Chi was highlighted as one of three types of intervention programs that are effective in reducing falls (on average delivered over 20 weeks, 71% group based, 7% tailored; Ng et al, 2019). Taken together, the 2019 Cochrane review and supplementary reviews of exercise as a single intervention among community-dwelling older adults found that Tai Chi is among the most effective strategies for preventing falls.…”
Section: Evidence From the Current Cochrane Review: Community-dwellinmentioning
confidence: 99%
“…It is believed that the mechanism by which exercise interventions prevent falls is by increasing standing and dynamic balance, strength and power, and coordination . While previous reviews have highlighted that there is more than one way to achieve these objectives (Ng et al, 2019;Sherrington et al, 2017), few studies have directly compared whether some exercise interventions are more effective than others in preventing falls. The Cochrane review of exercise-based interventions for preventing falls among community-dwelling older adults found little evidence for head-to-head comparisons of types of interventions.…”
Section: The Evidence For Tai Chi For Preventing Falls Relative To Otmentioning
confidence: 99%